Cold Dark Hydrogen as a Candidate for Dark Matter - Tatum, Eugene Terry; Lubashenko, Yury (European Journal of Applied Sciences, 2021)
Hydrogen is the most abundant element in the universe. While it is thought to be almost all accounted for within the baryonic sector, recent studies using new methods of observation have shown that this is not the case; the estimated density of cold, almost invisible, hydrogen turns out to be commensurate with the density of dark matter. As a result, a new situation has been created in cosmology, requiring a reassessment of the entire material composition of the universe. After carefully assessing the quality and quantity of cold hydrogen in the observable universe, the authors present a new model of ‘cold hydrogen dark matter’ (CHDM) herein. Cold hydrogen in the states described, including the intergalactic and interstellar vacuum densities cited in this paper, can explain practically all observed phenomena one typically associates with dark matter.